Photoprotection in pregnancy: addressing safety concerns and optimizing skin health - Lim, Henry W.; Piquero-Casals, Jaime; Schalka, Sergio; Leone, Giovanni; Trullàs, Carles; Brown, Anthony; Foyaca, Monica; Gilaberte, Yolanda; Krutmann, Jean; Passeron, Thierry (Frontiers in Medicine, 2025)
Pregnancy is associated with physiological skin changes, altered response to UV exposure and increased risk of pigmentary disorders such as melasma and linea nigra, which can impact quality of life. This review explores the effects of photoprotection during pregnancy, focusing on safety, efficacy, and the role of sunscreens in preventing pregnancy-associated hyperpigmentation and UV-induced skin damage. Sunscreen use in pregnant women is generally low, despite evidence supporting the benefits of broad-spectrum sunscreens to mitigate pigmentation changes and prevent DNA damage from UV exposure. Physiological changes during pregnancy influence sunscreen selection; ideally, sunscreens should be mineral-based, cosmetically acceptable, potentially supplemented with safe organic filters to optimize cosmetic acceptability and adherence, and free from ingredients associated with potential risks during pregnancy. Tinted sunscreens, which provide protection against high-energy visible light (HEVL), may offer enhanced prevention of hyperpigmentary disorders, and are recommended due to their added camouflage benefits, though shade options should ideally match diverse skin tones. Photoprotection strategy should include the use of wide-brimmed hats, sun-safe clothing and regular use of high-SPF, broad-spectrum sunscreens that protect against UVB, UVA, and HEVL. Tinted, mineral-based formulations potentially supplemented with safe organic filters may be optimal for pregnant women providing both effective protection and cosmetic benefits.